Socioformation: a necessary focus on university higher education - Ruiz-Aquino, Mely (2019)
This article deals with an analysis of the need to assimilate the paradigm of pedagogical innovation in universities: socioformation. Taking up the humanistic approach to education, and epistemology of complex thought. Because of urgency of forming new generations for the knowledge society. It is necessary to train students aware of their reality and capable of generating new knowledge and, to be better people. Undergraduates show optimal performance in solving problems in the context in which they live, in a position to insert themselves into the social, labor and technological world of this century, with environmental sustainability, improving living conditions and acting with commitment and respect in projects social, through the application of complex thinking and collaborative work. From a panoramic synthesis, theoretical and epistemological approach, methodology, basic features of the teaching profile and some logistical aspects to consider, aligned to this approach, are exposed. In conclusion, it is highlighted that competency-based training implies a paradigm shift compared to traditional education, based on the competency-based approach. Therefore, it seeks to generate reflection on pedagogical practices and adoption of socioformation in the curricular management of universities.